Big pumpkin - Silverman, Erica; Schindler, S. D. (New York : Aladdin Paperbacks, 1995)
A witch trying to pick a big pumpkin on Halloween discovers the value of cooperation when she gets help from a series of monsters.
"Aladdin picture books"--Cover.
350
350
Keywords: Witches -- Fiction; Pumpkin -- Fiction; Halloween -- Fiction; Witches -- Fiction; Monsters -- Fiction; Pumpkin -- Fiction; Halloween -- Fiction; Cooperativeness -- Fiction